144 Studying corticobasal syndrome across the UK via the BNSU. Issue 12 (14th November 2019) - Costantini, Alyssa; Jabbari, Edwin; Lamb, Ruth; Darvell, Marcia; Woodside, John; Rohrer, Jon; Lees, Andrew; Morris, Huw
Abstract : Background: There are a number of different causes of corticobasal syndrome (CBS) and we are recruiting CBS patients across the UK to the PROSPECT-UK study. Objective: To define patients with CBS and to define features that are helpful in determining the underlying pathological diagnosis. Methods: The RaDAR platform enables the recruitment of patients with CBS. Eligible patients are anonymously invited to contact the study team. Following informed consent, patients can participate remotely or be seen at their local study site. A subset of these patients undergo deep phenotyping, including CSF analysis for total Tau and Abeta. Results: We have established a cohort of 179 patients with CBS for future therapeutic, biomarkers and clinical studies. Mean recruitment is 5/month. The ABN RaDAR scheme has identified 58 CBS patients across the UK through 2018 so far, and we are liaising with consultants to recruit these patients. Deep phenotyping is underway – in patients with CSF analysis, 47% have an Alzheimer disease–like CSF profile highlighting the phenotypic diversity in this group. We are continuing to analyse other features of CBS. Conclusions: We are continuing to define the diverse pathological causes of CBS with a view to developing future disease modifying treatment trials.